2012
DOI: 10.3945/jn.111.154948
|View full text |Cite
|
Sign up to set email alerts
|

High Circulating Folate and Vitamin B-12 Concentrations in Women During Pregnancy Are Associated with Increased Prevalence of Atopic Dermatitis in Their Offspring

Abstract: Recent studies suggest that in utero exposure of methyl donors influences programming of the fetal immune system in favor of development of allergic disease. The aim of this study was to assess whether the MTHFR C677T polymorphism, folic acid supplementation, and circulating folate and vitamin B-12 concentrations during pregnancy were associated with wheezing, shortness of breath, and atopic dermatitis in offspring. The study was a population-based birth cohort from fetal life until 48 mo (n = 8742). The use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
6
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(144 citation statements)
references
References 40 publications
3
133
6
2
Order By: Relevance
“…Our findings that moderate folate levels in early pregnancy are associated with higher birth weight regardless of race/ethnicity are consistent with previous studies, [14][15][16][17][18][19][20][21][22][23][24]50 although an equally large number of studies from Europe, Asia and the US [25][26][27][28][29][30][31] have not confirmed these associations. Reasons for discordant findings are unclear.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings that moderate folate levels in early pregnancy are associated with higher birth weight regardless of race/ethnicity are consistent with previous studies, [14][15][16][17][18][19][20][21][22][23][24]50 although an equally large number of studies from Europe, Asia and the US [25][26][27][28][29][30][31] have not confirmed these associations. Reasons for discordant findings are unclear.…”
Section: Discussionsupporting
confidence: 80%
“…13 In humans, evidence of associations between maternal folate concentrations and fetal growth is conflicting, as high levels have been linked to both low and high birth weight, [14][15][16][17][18][19][20][21][22][23][24] while other studies found no associations. [25][26][27][28][29][30][31] Extremes of the birth weight distribution have been associated with a wide range of childhood and adultonset chronic diseases and conditions including obesity, impaired glucose tolerance, type 2 diabetes, coronary artery disease, congestive heart failure and some cancers.…”
Section: Introductionmentioning
confidence: 86%
“…In contrast to the negative findings for asthma in the Dutch studies, a case-control study of 1,962 Norwegian children (nested within a birth cohort) found a significant linear association between maternal plasma folate in the second trimester of pregnancy and asthma at age 3 years (38). Due to short duration of follow-up, both the second Dutch study (37) and the Norwegian study (38) are limited by potential misclassification of asthma.…”
Section: Epidemiologic Studies Of Folate Status and Asthma Or Atopymentioning
confidence: 84%
“…Although the overall results were consistent, and the phenotypic assessment of asthma was adequate, this study was limited by potential selection bias and nonassessment of folate status in the first or second trimester of pregnancy (36). A second, larger birth cohort study of Dutch children (n ¼ 8,742) found that nonfasting maternal plasma levels of folate or vitamin B 12 during the first trimester of pregnancy were significantly associated with increased odds of atopic dermatitis but not with asthma at age 4 years (37). In contrast to the negative findings for asthma in the Dutch studies, a case-control study of 1,962 Norwegian children (nested within a birth cohort) found a significant linear association between maternal plasma folate in the second trimester of pregnancy and asthma at age 3 years (38).…”
Section: Epidemiologic Studies Of Folate Status and Asthma Or Atopymentioning
confidence: 99%
See 1 more Smart Citation